SMART SYSTEM OF FAST INTERNET ACCESS DEVELOPMENT USING BACKBONE NETWORK METHOD - Verdi Yasin; Anindra Ramdhan Nugraha; Muhammad Zarlis; Ifan Junaedi (Journal of Information System, Informatics and Computing, 2018)
Backbone is a channel or high-speed connection that becomes the main path in a network. Network backbone is a network that connects multiple networks with low speed through the gateway. Backbone in the internet is a network that connects the network between countries and even between continents. With this internet backbone then we can connect with people in various parts of the world very easily and in a very short time. In addition, the coverage of this backbone is also very wide compared to other technology technologies. In addition, the backbone in the computer network also provides a huge range of benefits for computer users. System design is a part of a planning concept. Before doing the design, then first done the analysis process to be known and identified problems and needs that exist in the company related to what will be done and needed. In this case the system design for the manufacture of Internet backbone network. Development of Backbone Network is a network development method that has access capability to anticipate access problems in work system using internet network technology. Then the need for the ability of internet network support technology such as internet network Backbone model.